Detection of human papillomavirus DNA in urinary bladder carcinoma by in situ hybridisation. Issue 2 (1st February 1999) - De Gaetani, C; Ferrari, G; Righi, E; Bettelli, S; Migaldi, M; Ferrari, P; Trentini, G P
Abstract : AIMS: To investigate the sensitivity of an in situ hybridisation system to detect human papillomavirus (HPV) infection in transitional cell bladder cancer and to evaluate the advantages of analysing multiple biopsies; to examine the correlation between HPV tumour infection detected by in situ hybridisation and the presence of serum anti-HPV antibodies detected by enzyme linked immunosorbent assay (ELISA); and to relate the presence of viral infection to grade, stage, and follow up in cases of bladder cancer. METHODS: The in situ hybridisation technique was used with broad spectrum and type specific (6/11, 16/18, 31/33/35) probes against HPV DNA in formalin fixed, paraffin embedded tissues from 43 cases of bladder cancer. The results were analysed for the presence and type of papillomavirus and correlated with clinicopathological variables. RESULTS: The presence of HPV DNA was identified by the in situ hybridisation technique in 17 of 43 cases of bladder cancer; 12 of these were serum antibody positive and 10 had had multiple biopsies. Fifteen of the cases that were negative for HPV DNA by in situ hybridisation had positive serum serology when tested by ELISA. In 14 cases, the HPV was either types 16/18 or types 31/33/35, both of which carry high oncogenic risk. The stage (p < 0.05) and grade (NS) of the tumour and the outcome on follow up (p < 0.05) were correlated with the presence of HPV infection. CONCLUSIONS: ELISA is not useful in identifying patients with HPV positive bladder cancer, but the use of several probes and multiple biopsies increases the detection rate of HPV in neoplastic tissues. The association between tumour virus infection and high grade/high stage tumours and worse outcome suggests that HPV infection of neoplastic tissue has a negative effect on the behaviour and evolution of transitional cell bladder carcinoma.